Cultural competence, professional values, and spiritual well-being in nursing interns: a descriptive cross-sectional study - Amir Mohamad Nazari; Seyedeh Narjes Mousavizadeh; Zahra Khorrami Khoramabadi; Vahid Yousofvand; Seyed Mohammad-Javad Ghazavi Dozein (BMC Nursing)
Abstract Background Cultural competence, professional values, and spiritual well-being are among the topics that are widely considered today in response to turbulent and complex environments in organizations. The purpose of this study was to investigate the relationship between cultural competence, professional values, and spiritual well-being of nursing interns. Methods In this study, a total of 200 nursing interns affiliated with universities of medical sciences in Tehran city (Tehran, Shahid Beheshti, and Iran) were included as participants. They were selected through convenience sampling. Data collection tools were the Medical Science Graduates’ Cultural Competence Questionnaire, The Nurses Professional Values Scale-Revised (NPVS-R), and the Spiritual Well-Being Scale (SWBS). Results The mean scores of cultural competence, professional values, and spiritual well-being of nursing interns were 151.26 (7.14), 74.24 (10.62), and 71.23 (8.45), respectively. There was a significant relationship between cultural competence and professional values (r = 0.460, p < 0.001), and cultural competence and spiritual well-being (r = 0.489, p < 0.001) of nursing interns. The variables of professional values (β = 0.297, p < 0.001), spiritual well-being (β = 0.350, p < 0.001), and moderate economic status (β=-0.213, p = 0.005) were the most effective predictors of nursing interns’ cultural competence. Conclusion The cultural competence of nursing interns is influenced by their professional values and spiritual well-being. By implementing suitable educational strategies and providing support, educational managers can enhance the cultural competence of nursing interns. Clinical trial number Not applicable.